1988
DOI: 10.1149/1.2095883
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed Electrodeposition of Ni‐Mo Alloys

Abstract: The effect of pulsing the current on the composition, the internal stress, and mechanical properties of Ni‐Mo electrodeposits was investigated. The molybdenum, content increased with increasing peak current density and to a lesser degree with decreasing duty cycle. A reduction in the internal stresses was explained in terms of the relaxation of those due to crystallite or fine grain coalescence during the off‐time and an expansion of the surface layer when hydrogen diffused into it at the start of each on‐time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
38
0
1

Year Published

1988
1988
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(41 citation statements)
references
References 6 publications
2
38
0
1
Order By: Relevance
“…Hence, the pulse electrodeposited Si electrodes were directly assembled in a 2025 coin cell without The SEM analysis (Figure 2) of the samples shows a drastic change in morphology between the films deposited at 0 (galvanostatic, PEDSi-0), 500 (PEDSi-500) and 1000 Hz (PEDSi-1000). PEDSi-0 (Figure 2c) which corresponds to the constant current electrodeposition showed islands of silicon approximately 5-10 µm wide simulating dried mud cracks, which is in good agreement with previous study reported [37]. PEDSi-500 (Figure 2d) which corresponds to pulse current frequency of 500 Hz, showed a cracked morphology very similar to PEDSi-0, however, the solid islands of Si were replaced by discrete particulate deposits.…”
Section: Electrochemical Characterization Of Pedsi On Cusupporting
confidence: 90%
See 1 more Smart Citation
“…Hence, the pulse electrodeposited Si electrodes were directly assembled in a 2025 coin cell without The SEM analysis (Figure 2) of the samples shows a drastic change in morphology between the films deposited at 0 (galvanostatic, PEDSi-0), 500 (PEDSi-500) and 1000 Hz (PEDSi-1000). PEDSi-0 (Figure 2c) which corresponds to the constant current electrodeposition showed islands of silicon approximately 5-10 µm wide simulating dried mud cracks, which is in good agreement with previous study reported [37]. PEDSi-500 (Figure 2d) which corresponds to pulse current frequency of 500 Hz, showed a cracked morphology very similar to PEDSi-0, however, the solid islands of Si were replaced by discrete particulate deposits.…”
Section: Electrochemical Characterization Of Pedsi On Cusupporting
confidence: 90%
“…The pulse power electrodeposition approach offers an economical and easy way to change the grain size and morphology of the deposits, thus enhancing the density of coatings and their mechanical strength and corrosion properties [36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%
“…One of the reasons for using a pulse rather than dc plating voltage is that pulse voltage can suppress plating thickness nonuniformity. [1][2][3][4][5] In contrast, this paper deals with an application wherein nonuniform plating thickness induced by surface condition variations is a desirable feature.Electroplating is the commonly used method of fabricating metal contacts of thickness Ͼ2 m on semiconductor substrates. This paper presents the interesting plating nonuniformities introduced by dc and PR plating waveforms on semiconductor substrates in which the doping polarity varies over the semiconductor surface.…”
mentioning
confidence: 99%
“…One of the reasons for using a pulse rather than dc plating voltage is that pulse voltage can suppress plating thickness nonuniformity. [1][2][3][4][5] In contrast, this paper deals with an application wherein nonuniform plating thickness induced by surface condition variations is a desirable feature.…”
mentioning
confidence: 99%
See 1 more Smart Citation